2021
DOI: 10.1029/2021ja029518
|View full text |Cite
|
Sign up to set email alerts
|

Thin Current Sheet Behind the Dipolarization Front

Abstract: In the near-Earth magnetotail, a major energy conversion process takes place associated with dipolarization and localized fast flows, called bursty bulk flows (BBFs) containing minute-scale flow bursts (FBs; e.g., Angelopoulos et al., 1994;Baumjohann et al., 1989) with a mesoscale (few R E : Earth radii) dawn-dusk size (R. Nakamura et al., 2004) that can ultimately affect the large-scale magnetotail dynamics (Sergeev et al., 2012, and reference therein). These localized BBFs contain sharp enhancements in Bz (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 70 publications
(148 reference statements)
4
5
0
Order By: Relevance
“…It clearly shows three pairs of 𝐴𝐴 𝐴𝐴‖ , a R2-sense pair in the region earthward of −16 Re with the magnetic field lines "1" and "2" passing through it, a horseshoe-shaped R1-sense pair with the magnetic field lines "3" and "4" passing through it, and an R0-sense loop with the magnetic field lines "5" and "6" passing through it. That R0-sense FAC loop expanding from −20 to −30 Re in the tail is also supported by the Cluster-MMS observations (Figure 5 in Nakamura et al, 2021). In an MHD simulation (Birn et al, 2020), a similar R0-sense FAC loop is found to be inertia dominated and associated with the fast flows during the injection.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 71%
See 2 more Smart Citations
“…It clearly shows three pairs of 𝐴𝐴 𝐴𝐴‖ , a R2-sense pair in the region earthward of −16 Re with the magnetic field lines "1" and "2" passing through it, a horseshoe-shaped R1-sense pair with the magnetic field lines "3" and "4" passing through it, and an R0-sense loop with the magnetic field lines "5" and "6" passing through it. That R0-sense FAC loop expanding from −20 to −30 Re in the tail is also supported by the Cluster-MMS observations (Figure 5 in Nakamura et al, 2021). In an MHD simulation (Birn et al, 2020), a similar R0-sense FAC loop is found to be inertia dominated and associated with the fast flows during the injection.…”
Section: Discussion and Concluding Remarkssupporting
confidence: 71%
“… Overview of Cluster and MMS observations for 8 September 2018, 14:00–14:05 UT (top, adapted from Nakamura et al., 2021), and RCM‐MHD simulation results for 00:32–00:42 (bottom). (a1)/(a2) locations of Cluster and MMS satellites/two probe points in the simulated equatorial B Z distribution; (b1)/(b2)/(e1)/(e2) magnetic field; (c1)/(c2)/(f1)/(f2) electric field E Y ; (d1)/(d2)/(g1)/(g2) cross‐tail current density J Y .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This stretching of the magnetic field is highly localized in the dawn‐dusk direction, limited to ∼5 R E at most, and it can create x‐lines that last on the order of ∼10 min. Thin current sheets have been observed as part of the rebounding process (Nakamura et al., 2021; Panov et al., 2010) and they could lead to reconnection in a similar manner. However, to the authors' knowledge, these x‐lines have not been directly observed.…”
Section: Discussionmentioning
confidence: 98%
“…The scale of the DF is usually on the order of the ion inertial length or the ion gyroradius (Runov et al 2009;Zhou et al 2009;Fu et al 2012;Huang et al 2012Huang et al , 2015aHuang et al , 2015b. The DF is closely related to the dynamic processes of the magnetotail and it plays a vital role in particle acceleration (Deng et al 2010;Fu et al 2011Fu et al , 2013Fu et al , 2019Huang et al 2012Huang et al , 2019Zhou et al 2013;Nakamura et al 2021), energy conversion (Huang et al 2012(Huang et al , 2015bAngelopoulos et al 2013;Zhong et al 2019), as well as magnetic flux and mass and energy transport (Angelopoulos et al 1994(Angelopoulos et al , 2002Nakamura et al 2009;Liu et al 2014) in the magnetotail. Previous studies suggested that the DF is a signature of unsteady magnetic reconnection (Sitnov et al 2009;Fu et al 2013).…”
Section: Introductionmentioning
confidence: 99%